The effect of electric spot-welding on the mechanical properties of different orthodontic wire alloys - Nascimento,Leonard Euler Andrade Gomes (2012)
The aim of this study was to test the hypothesis that there is a direct relationship between surface structure and tensile strength of orthodontic alloys submitted to different levels of welding current. Three types of alloys were assessed. One hundred and eight cross-sectional test specimens ("X") were made, 18 for each wire combination, and divided into 6 groups: SS (steel-steel); SN (steel-NiTi); SB (steel-Beta-Ti); NN (NiTi-NiTi); NB (NiTi-Beta-Ti) and BB (Beta-Ti-Beta-Ti), submitted to 6 spot-welding procedures at different levels of current (Super Micro Ponto 3000). Student-Newman-Keuls, Wilcoxon signed-rank, and Kruskal-Wallis tests were used (p < .05). Statistical difference was found between SN group and all the other alloy combinations (p < .05). Initial roughness of alloys ranged from .04 to .55 Ra, with statistical difference between groups (p < .001). The hypothesis was rejected and the tensile strength of Ti-alloys combinations Steel × Beta-Ti was significantly affected by the current level at P50, which changed the properties and structure of the wires.